Fiscal Deficit and Economic Growth in Nigeria: Ascertaining a Feasible Threshold - Aero, Oluwafadekemi; Ogundipe, Adeyemi A. (International Journal of Economics and Financial Issues, 2018)
This study investigates the effects of fiscal deficits on Nigeria economic growth from 1981-2014. The study established an optimal fiscal deficit level using the Threshold Autoregressive (TAR) model. The empirical analysis supported the existence of a significant positive relationship between economic growth and the regressors – capital, labour, inflation rate, and trade openness. On the other hand, the study found that a significant negative relationship exists between fiscal deficits, financial depth and economic growth in Nigeria. The study established a threshold level of 5% which is conducive for economic growth at a lag of one year, for the Nigerian economy. Aligning this finding to the present reality, it is hence concluded that the Nigerian economy has been characterized by continuous fiscal deficits, which has not positively contributed to economic growth. The study, therefore, recommends that the government should increase capital spending and ensure that an optimal fiscal deficit bracket level of 5% is maintained. Keywords: Fiscal Deficit, Growth, TAR, Nigeria JEL Classifications: E62, H62, O4